Comprehensive analysis of the clinical significance, immune infiltration, and biological role of MARCH ligases in HCC - Cao, Jun; Tu, Dao-yuan; Zhou, Jie; Jiang, Guo-qing; Jin, Sheng-jie; Su, Bing-bing; Tang, Hao; Tang, Yu-hong; Wang, Ao-qing; Wang, Qian; Liu, Ren-jie; Zhang, Chi; et al. (Frontiers in Immunology, 2022)
The membrane‐associated RING‐CH (MARCH) family, a member of the E3 ubiquitin ligases, has been confirmed by a growing number of studies to be associated with immune function and has been highlighted as a potential immunotherapy target. In our research, hepatocellular carcinoma (HCC) patients were divided into C1 and C2 MARCH ligase-related patterns by the non-negative matrix factorization (NMF) algorithm. Multiple analyses revealed that the MARCH ligase-related cluster was related to prognosis, clinicopathological characteristics, and the tumor immune microenvironment (TIME). Next, the signature (risk score) of the MARCH prognosis was constructed, including eight genes associated with the MARCH ligase (CYP2C9, G6PD, SLC1A5, SPP1, ANXA10, CDC20, PON1, and FTCD). The risk score showed accuracy and stability. We found that the correlations between risk score and TIME, tumor mutation burden (TMB), prognosis, and clinicopathological characteristics were significant. Additionally, the risk score also had important guiding significance for HCC treatment, including chemotherapy, immunotherapy, and transarterial chemoembolization (TACE).